Adolescent and family development: Autonomy and identity in the digital age. (November 2016) - Shifflet-Chila, Erica D.; Harold, Rena D.; Fitton, Victoria A.; Ahmedani, Brian K.
Abstract: Adolescence is a time when youth are faced with multiple tasks that intersect and influence one another, e.g., increased desire for autonomy, salience of identity issues, peer orientation, self-focus and self-consciousness, and a continuing need for a safe environment in which to explore autonomy and identity. These all occur in a dynamic ecosystemic environment, which in the past would have mostly included family, peers, and school, but today also includes cyberspace as both a system, and a means to interact with many other systems through the use of multiple forms of information technology (IT). This paper uses the voices and experiences of 128 adolescents, captured in qualitative interviews, to look at autonomy and identity in the digital age as they talk about their parents vis à vis their use of IT. Thematic analysis revealed two major themes: 1) Adolescents spoke of their expertise. In particular they commented on their knowledge to repair equipment, ability to use IT well, their sense of pride in their own ability and their parents' acknowledgement of this ability. 2) Subjects perceived little need for their own supervision, but assessed that other adolescents and younger children needed to be watched closely by their parents. Implications of this work are discussed. Highlights: Adolescence occurs in a dynamic ecosystemic environment that includes cyberspace. Adolescents recognize and value their technology expertise. Adolescent IT expertise may speed up the life task of separation and individuation. Adolescents see little need for their tech-related activities to be supervised. Adolescents report the need for supervision of children younger than themselves.